Model Regresi Logistik pada Kelulusan Ujian Sertifikasi Pengadaan Barang dan Jasa Pemerintah - Rukini Rukini (Jurnal Ekonomi Kuantitatif Terapan, 2016)
The regression model a means to analyze the relationship between response variable and the predictor variables. Logistic regression model is used when response variable is qualitative. The appropriate model obtained after parameter estimation, significance test and compatibility test models. The goal of this research was to determine the effect of age, years of service and gender of participants exams towards graduation. The case study certification exams government procurement of goods and services to wave II Pusdiklat BPS RI  Year 2015. The data used as many as 194 people. The processing results show that age has a significant influence on level the graduation certification exams of government procurement of goods and services. The more participants certification exam government procurement of goods and services for less than 35 years of age , the increasing tendency to pass.